Perineal Groove: A Rare Congenital Anomaly - Barbosa, Manuel (2016)
Perineal groove is a rare congenital anorectal malformation, with incidence yet undetermined. It is almost exclusive to the female newborn and its embryogenic origin remains uncertain. We present a case-report of a newborn girl that was discharged from the nursery without complications. At her first appointment at primary care we noted a wet sulcus connecting the posterior vaginal commissure and the anus. This case report emphasizes the rarity of the perineal groove and the importance of a good quality history and physical examination at primary care.